Verbalization of Temporal Relations in the Ukrainian Language: Linguo-Didactic Aspect - Зайченко, Н.; Юденко, О. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
One of the possible models of linguo-didactic interpretation of language material – from typical meanings to means of their expressions in a studied (specific) language – is represented in the article in terms of verbalization of temporal relations in the Ukrainian language. The Ukrainian language is characterized by a ramified system of means of expression in temporal relations: morphologic, grammatical, and lexical ones. They interact diversely in the situations of natural communication determining verbal behaviour of the participants of communication within a framework of “physical” time. The wide variety of temporal meanings taking into account communicative tasks and specific situations of communication has been systematized into nine semantic groups. The featured classification reflects both the essential characteristics of objective time, i.e. cycle of operation and linearity, and peculiarities of their specification in speech, i.e. simultaneity or asynchronicity with its modification of precedence and succession of actions in time. Methodically relevant linguistic characteristics, peculiarities of functioning specifics such as synonymic means of expression of temporal meanings in simple and complex sentence, which are necessary to take into account for prevention of possible errors in the speech of foreign students, are identified in each group. The article contains the fragmentary description of three groups of standard temporal meanings: 1. Correlation of actions (events) in time, precedence and succession. 2. Period of time during which a certain action (event) takes place. 3. Duration of an action (How long? How much time?) The offered approach to the verbalization of the temporal relations is not only used for the other types of logical and notional relations – purpose, reason, etc., but for the universal description of the Ukrainian language in order to study it as a foreign language. Such a linguistic description turns out to be a reliable reference point for a teacher determining optimal ways and means for its presentation during classes in accordance with the external conditions of teaching. The given universal model for description has been implemented in a study guide of one of the authors. It can also serve as a reference point for a nationally oriented presentation of language material.